(untitled) (Journal of Universal Science Research, 2024)
This is the abstract of Chemical terminology, names of chemical elements acids and oxides. In this article, I have mentioned about the chemical terminologies of the elements some of the important acids and oxides. I have also mentioned about the uses of these substance in our body how they help in various metabolic activities etc.